Transcutaneous Bone-anchored Hearing Aids Versus Percutaneous Ones: Multicenter Comparative Clinical Study. Issue 5 (June 2015) - Iseri, Mete; Orhan, Kadir Serkan; Tuncer, Ulku; Kara, Ahmet; Durgut, Merve; Guldiken, Yahya; Surmelioglu, Ozgur
Abstract : Objective: The aim of this study is to compare the clinical audiological outcomes as well as patient satisfaction of bone-anchored, hearing aid surgery between the percutaneous Dermalock and the transcutaneous Attract systems. Study Design and Methods: This is a multicenter, retrospective clinical study. The patients who underwent Baha Dermalock and Baha Attract surgery were analyzed for hearing results, surgical complications, and postoperative follow-up specifications for both systems. Speech reception thresholds and bone conduction thresholds with and without aided conditions were evaluated. Patient satisfactions were also determined for both groups by Glasgow Benefit Inventory questionnaire. Results: Both of the groups had some minor complications such as skin irritations around the abutment and skin erythema over the magnet. Both of the groups benefit from the devices audiologically; however, when the groups were compared, better results were observed in the percutaneous, bone-conduction group. Conclusion: We can confirm that both transcutaneous and percutaneous techniques are effective in the rehabilitation of conductive hearing loss when conventional hearing aids cannot be used. However, both of the systems have some advantages and limitations in terms of audiological and surgical perspectives.